The Cultural Meaning of Philosophy - Krakauskas, Edmundas (Problemos, 1995)
Philosophy is a result of creative work and as such also a factor of that work. The philosophy which pretends to be absolute truth loses the sense of measure and depreciates the man. Such is the fate of the dogmatized materialistic philosophy. It became a hindrance to the development of profound philosophical thought and because of its ignorance of existence of national cultures – a source of wisdom. A philosophical thought arises in a crossing of different cultures. It represents an example of the spontaneous thinking and of an originality of certain culture. The cultural meaning of philosophy is underlined by those accents that are expressing its humane trend.